MANAJEMEN PENDIDIKAN ANAK USIA DINI/PAUD - Dwita Darmawati; Bambang Subekti; Sumarsono Sumarsono (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2009)
This study aims to find out and analyze in depth how the strategic management of early childhood in North Purwokerto district Banyumas. The strategy used in this research is case study. The data required is about the history and development of early childhood up, Vision, Mission, Goals and strategies, early childhood programs, data on the implementation of early childhood, data on customer satisfaction. These data were collected through interviews, observation and questionnaires. Based on data analysis and discussion, concluded that the strategic formulation in early childhood usually do not go well. The study also concluded that the performance aspects of early childhood visits from satisfied customers (parents) in general is good. This study provides implications, the need for long-term strategy formulation, or surveys of consumers with different indicators.